communication Communication of the Innovation Movement Program to Popularize Fish Eating (GEMARIKAN) in Tanjung Redeb Village, Berau Regency: Communication of the Innovation Movement Program to Popularize Fish Eating (GEMARIKAN) - tri ningsih; Erwiantono; Qoriah Saleha (2339-1324, 2024)
The research was conducted with the aim of analyzing and describing how the GEMARIKAN program innovation communication process in Tanjung Redeb Village. The research was carried out for 12 months from November 2021 to October 2022 in the Tanjung Redeb Village, Berau Regency. The sampling method used was purposive sampling method with 17 respondents. The analytical method uses a qualitative descriptive analysis with a case study approach. The focus of this research is the 4 elements of innovation diffusion, namely innovation with the stages of knowledge, persuasion and decision, implementation, and confirmation, as well as communication channels, timeframe, and social systems. Data collection techniques used were observation, interviews and review of document contents. The stages of innovation in the process of adopting innovation are: The stage of public knowledge acquires knowledge through socialization. The most effective approach to the persuasion stage is the approach through fish processing training. In the implementation phase, the community implements the GEMARIKAN program by making processed fishery products. In the confirmation stage, the entire community implements the GEMARIKAN program. Communication channels, the majority of people use interpersonal media. The social system of the majority of people is included in the Early Majority recipient group.